Time-domain simulation of berthing problem between FPSO and shuttle tanker in waves. (June 2016) - Nam, B.W.; Kim, Y.; Hong, S.Y.
Graphical abstract: Highlights: Numerical method for berthing problem between two floating bodies in waves is proposed. The finite element method with efficient re-mesh algorithm is applied. The berthing problem between FPSO and shuttle tanker in waves is investigated. The focus is on the wave-induced motion response during the berthing operation. Abstract: A time-domain simulation method based on potential flow model has been developed to investigate the berthing problem between two floating bodies in wave. The boundary value problem is formulated with respect to an earth-fixed coordinate system because the relative positions of the two vessels continuously change during the berthing operation. The classical finite element method is used to solve the Laplace equation in the fluid domain with moving boundary. The linearized free-surface boundary conditions are integrated in time by applying 4th-order Adams–Bashforth–Moulton method. A simple re-mesh algorithm with local and global mesh systems is introduced to update mesh by considering large horizontal movement of the berthing vessel. The developed numerical method is used to investigate the berthing problem between a FPSO and shuttle tanker in waves. The focus is on the wave-induced motion response during the berthing process. The characteristics of the motion responses in berthing operation are examined with various wave frequencies, berthing speeds and wave headings.